Transcripthomic response of Atlantic salmon (Salmo sailor) to the chalices development stage of Chilean sea lice (Caligus rogercresseyi) - Neumann-Oyarzo, Karen Flora (2020)
The sea louse Caligus rogercresseyi is the most important copepod ectoparasite responsible for significant economic losses in Chilean salmon industry. The impact of sea louse is related to loss of final product quality, mainly due to the activities of both settling and feeding of the parasites on the skin, which also produces a lengthening of the production cycle, increase susceptibility to other pathogens and treatment costs. Furthermore, recent years have seen increased both count lice per fish and lice resistance to drug treatment, so it is necessary to look for alternative ways to improve the resistance of the host. Despite the economic impact of sea lice C. rogercresseyi in Chilean salmon farming, there is limited information about their biology and behavior, and mostly the biological response of salmonids to them. The aim of the study is to determine the transcriptomic response by RNA-Seq of Atlantic salmon (Salmo salar) to de sea louse Caligus rogercresseyi. The results indicate that there would be a difference in the response both local and systemic of Salmo salar with high and low susceptibility to infestation. This study contributes to the understanding of transcriptomic profile of Salmo salar associated with sea lice resistance, where several pathways could be involved in the low susceptibility to infestation, some of them related to the tissue repair and/or activity of the fish, maintaining the functional integrity of the skin, energy metabolism, availability of iron and oxygen, and immune response. El piojo de mar Caligus rogercresseyi es el más importante copépodo ectoparásito responsable de pérdidas económicas significativas de la industria del salmón Chilena. El impacto del piojo de mar está relacionado con la pérdida de calidad del producto final debido principalmente a las actividades de fijación y alimentación de los parásitos sobre la piel, alargamiento del ciclo productivo, incremento a la susceptibilidad a otros patógenos y costos del tratamiento. Además, los últimos años se ha registrado ...